Transport and accumulation of floating marine litter in the Black Sea: insights from numerical modeling - Castro-Rosero, Leidy M.; Hernandez, Ivan; Alsina, José M.; Espino, Manuel (Frontiers in Marine Science, 2023)
Introduction Floating marine litter (FML) is a global problem with significant risks to marine life and human health. In semi-enclosed basins like the Black Sea, slow water replenishment and strong input from European rivers create conditions that can lead to the accumulation of FML. This study aims to validate and utilize an FML dispersion and accumulation numerical model. Additionally, it assesses the influence of Stokes drift on the accumulation patterns of marine litter in the Black Sea, focusing on the contribution from the main river discharge points. Methods Numerical Lagrangian modeling adapted to the regional domain in the Black Sea was employed to simulate the dispersion and accumulation of FML. Three scenarios were conducted: two involved homogeneous particle release, one considering Stokes drift, and the other excluding it. The third scenario involved particle release from the nine main river basins. Results The southwest coast of the Black Sea exhibited a high density of FML in all scenarios. This finding is likely attributed to the cyclonic circulation, significant FML input from the Danube River, and other northern rivers. Notably, the consideration of Stokes drift significantly impacted the residence time of particles in offshore waters and the percentage of particles washing up on the shore. Including Stokes drift increased the percentage of beached particles from 45.5% to 75.5% and reduced the average residence time from 99 to 63 days. These results align with recent literature, which emphasizes the importance of accounting for Stokes drift to avoid overestimating residence times. Discussion The model's findings provide valuable insights into FML accumulation patterns in the Black Sea. The eastern region near the Georgian coast and the northwestern Black Sea were identified as high-density areas, corroborated by observational data. This research underscores the significance of considering Stokes drift when modeling FML transport, particularly concerning marine litter accumulation and potential impacts on coastal regions.